Henri III épistolier : rhétorique royale de la lettre familière - Vaillancourt, Luc (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2008)
It might seem surprising to find, in a royal correspondence dedicated primarily to the task of public administration, elements of informal expression, an obvious informal tone of personal concern, and even numerous signs of friendly consort. Since the royal person remains indistinguishable from his function, he avoids with greater difficulty than others the hierarchical imperatives that determine epistolary exchanges. Even so, the letters addressed by Henry III to his court favourites and to state secretary Villeroy are particular in that they exhibit an exemplary sociability that invites reciprocity within the master-servant relationship. The present article aims to show that this rhetoric of familiarity contributes to an expression of favour which strengthens a privileged mode of communication, which constitutes a real pact of fidelity. Indeed, epistolary correspondence is seen as much more than a simple administrative expedient, or a means of long-distance communication. It is seen rather as a political technique which is useful in serving the mutual interest of the correspondents.